The enriched mind: cognitive stimulation and behavior in non-human primates - Mota-Rojas, Daniel; Whittaker, Alexandra L.; Coria-Avila, Genaro A.; Domínguez-Oliva, Adriana; Bienboire-Frosini, Cécile; Hernández-Avalos, Ismael; Chávez, Cuauhtémoc; Olmos-Hernández, Adriana; Martínez-Burnes, Julio; García-Herrera, Ricardo; Mora-Medina, Patricia; Grandin, Temple (Frontiers in Veterinary Science, 2025)
Non-human primates (NHPs) possess high cognitive abilities that enable them to respond effectively to complex social, ecological, and psychological challenges. These abilities need to be stimulated in non-human primates under human care in zoos, conservation centers/sanctuaries, or research facilities, where stereotypies and behavioral and/or psychobiological disturbances are frequently associated with captivity. Cognitive enrichment (CE), a type of environmental enrichment that facilitates decision-making skills, problem-solving, and control over the environment, is one way to promote primate welfare by encouraging engagement in cognitive tasks. Currently, non-technological and technological cognitive enrichments are implemented for NHPs under human care to enhance positive behavioral responses and prevent negative emotional states such as boredom or stress. The present review aims to analyze the benefits that CE provides to NHPs (including monkeys and great apes), highlighting its relevance to research, conservation, and ethical management in controlled environments.